Traditional Media in the Digital Age: Survival Strategies and Economic Challenges - Shehu, Ummul-Khayr Saleh; Mohammed, Binta Kasim; Dogo, Mendos Bala; Joseph, Ayodele B.; Sani, Muhammad Hamisu (NIU Journal of Humanities, 2026)
This research looks at the survival strategies and economic issues facing traditional media in the digital era. The internet, artificial intelligence, social media and mobile connections have revolutionized how people consume media, and the traditional revenue models of newspapers, radio and television stations are now under threat. The study examines the economic challenges traditional media are currently facing, how well adaptation strategies are working, and how data privacy laws and concepts of “free news” affect digital monetization, using a desk-based qualitative research methodology based on the analysis of secondary data from published scholarly articles, reports and industry publications. The research is based on the Technological Determinism Theory that states that technology has revolutionized media production, distribution and audience engagement. The analysis shows that traditional media's financial sustainability is hampered by the decline in advertising revenues, fragmentation of audiences, high operating costs, digital competition, and shifting consumer tastes. The study also reveals numerous companies are adopting digital transformation tactics like subscription models, sponsored content, integration of social media, streaming, platforms-first and audience engagement strategies. But, barriers like lack of digital infrastructure, skills, and rigid data privacy regulations remain in the way of successful monetization. The study's findings indicate that traditional media's future is contingent upon constant innovation, diversified revenue streams, strategic digital investments and a long-term commitment among traditional media to credible journalism. It makes recommendations for greater investment in digital infrastructure, staff training, an audience-first content strategy, and privacy-preserving monetization models that will help sustain in the changing media landscape.